EDUKASI PERPAJAKAN DAN PELATIHAN PENGHITUNGAN PAJAK PUSAT SISWA-SISWI SMAN 20 KAB.TANGERANG - Kurniawati, Herni; Sari, Vinetta Ratna; Lie, Irene Kim (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2023)
The direction of the Minister of Finance and the Minister of Education and Culture for the younger generation starting at the elementary, junior high and high school levels are already tax literate by creating a tax-aware and intelligent generation to understand the importance of the role of taxes in Indonesia as a source of state revenue apart from the oil and gas sector for the welfare of the people. PKM is intended to help Partners understand the science of taxation, which is part of Accounting Economics. In Indonesia, the central tax which is managed centrally by the Ministry of Finance through the DGT, consists of Income Tax, Value Added Tax, Land and Building Tax, Stamp Duty, and Sales Tax on Luxury Goods. PKM uses primary and secondary data, where primary data is obtained directly from Partners, such as data from interviews with school principals and teachers as well as data in the form of information to what extent students understand taxes. PKM utilizes secondary data from journal articles, internet news sources, and books to support PKM. The results of PKM PKM activities have been carried out on Friday 12 May 2023 at 10.00 WIB until finished, offline by visiting schools with students as part of PKM. The outputs of PKM activities are presentations in national seminars as speakers, and articles uploaded by PINTAR as additional output.